Differences in the psychological portrait of a sociopath, sociophobe and introvert - L. Spytska (Mukachevo State University, 2023)
The relevance of the problem is the need to highlight specific differences in the psychological portraits of a sociopath, sociophobe and introvert to distinguish clearly between seemingly similar concepts. The purpose of the research is to detail the specific features of human mental states, to establish the differential characteristics of a sociopath, sociophobe and introvert, and to distinguish each of these states as a separate independent component of the human psyche. Statistical and analytical methods were used to obtain the necessary results. The main markers of sociophobic behaviour are considered, and it is noted that they can manifest themselves with varying intensity depending on the severity of the symptoms of sociophobia. The author presents a psychological portrait of a sociopath and defines the typology of sociopathy. The main features of an introverted personality are identified, the advantages that introverts have in comparison with extroverts and the main forms of their maladjustment are considered. The specific framework of each concept examined is highlighted, and the differences between them are indicated. It is substantiated that introversion appears in humans from birth and is associated with the specific structure of the brain, while sociopathy and sociophobia are acquired throughout life as a result of psychological and physiological trauma. It is identified that a sociophobe and a sociopath differ in psychological characteristics, as a sociophobe is afraid of people, and a sociopath hates people. It is proved that, unlike sociophobia and sociopathy, introversion is not a mental disorder, but an element of a healthy psyche. The practical significance of the research is that the results will help to distinguish the psychological states of a person, to understand and differentiate the analysed concepts more clearly, to preliminarily determine one's psychological state, to establish a specific framework for a simplified psychologist's conclusion, and to identify important details and features of the manifestations of a sociopath, sociophobe and introvert.